The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26185633
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Distribution of Toltrazuril and Toltrazuril Sulfone in Plasma, Intestinal Tissues and Content of Piglets after Oral or Intramuscular Administration

Abstract: Piglet coccidiosis due to Cystoisospora suis is a major cause of diarrhea and poor growth worldwide. It can effectively be controlled by application of toltrazuril (TZ), and oral formulations have been licensed for many years. Recently, the first parenteral formulation containing TZ in combination with iron (gleptoferron) was registered in the EU for the prevention of coccidiosis and iron deficiency anemia, conditions in suckling piglets requiring routine preventive measures. This study evaluated the absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In addition, Karembe et al reported the disposition kinetics of toltrazuril and ponazuril in plasma and the intestinal tissues after oral and intramuscular application of toltrazuril in piglets. This study observed that after the metabolism of toltrazuril to ponazuril, both showed significant and sustained concentrations in the jejunal tissue where C. suis mainly colonize, as well as in the intestinal contents ( 49 ). We have not yet obtained sufficient data to demonstrate the mechanisms involved in the higher and more sustained plasma, tissue, and fecal concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Karembe et al reported the disposition kinetics of toltrazuril and ponazuril in plasma and the intestinal tissues after oral and intramuscular application of toltrazuril in piglets. This study observed that after the metabolism of toltrazuril to ponazuril, both showed significant and sustained concentrations in the jejunal tissue where C. suis mainly colonize, as well as in the intestinal contents ( 49 ). We have not yet obtained sufficient data to demonstrate the mechanisms involved in the higher and more sustained plasma, tissue, and fecal concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…administration was higher than the p.o. administration (Karembe et al, 2021). In the current study, we measured the central pharmacokinetics and tissue (muscle and liver in addition to jejunum) distributions of TZR and TZR‐SO 2 after p.o.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction procedures were based on previously published methods (Karembe et al, 2021; Soliman, 2015) with slight modifications. Briefly, frozen serum samples were thawed at room temperature, then 400 μL of ethyl acetate was added to 200 μL of the serum sample and vortexed for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations